2019
DOI: 10.1037/ser0000239
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of synchronous telepsychology interventions for people with anxiety, depression, posttraumatic stress disorder, and adjustment disorder: A rapid evidence assessment.

Abstract: Telepsychology holds promise as a treatment delivery method that may increase access to services as well as reduce barriers to treatment accessibility. The aim of this rapid evidence assessment was to assess the evidence for synchronous telepsychology interventions for 4 common mental health conditions (depression, anxiety, posttraumatic stress disorder, and adjustment disorder). Randomized controlled trials published between 2005 and 2016 that investigated synchronous telepsychology (i.e., telephone delivered… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
140
0
9

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 239 publications
(174 citation statements)
references
References 43 publications
10
140
0
9
Order By: Relevance
“…In the opening editorial, Elliott (2020) identifies another of the most substantial barriers to the adoption of telepsychology: ourselves. Psychologists' bias against telepsychology can at times be profound, yet that bias runs counter to the overwhelming evidence suggesting that telepsychology is no less effective than in‐person treatment for the vast majority of presenting concerns (Varker, Brand, Ward, Terhaag, & Phelps, 2019) and that it can be an excellent extension to in‐person services such as aiding in assessment (Heesacker, Perez, Quinn, & Benton, 2020). Some seemingly obvious exceptions to this general rule may apply for specific clinical services, such as neuropsychological assessment, although evidence is mounting that certain neuropsychological assessments can feasibly be administered through telepsychology (Galusha‐Glasscock, Horton, Weiner, & Cullum, 2016).…”
Section: Telepsychology Special Issuementioning
confidence: 99%
“…In the opening editorial, Elliott (2020) identifies another of the most substantial barriers to the adoption of telepsychology: ourselves. Psychologists' bias against telepsychology can at times be profound, yet that bias runs counter to the overwhelming evidence suggesting that telepsychology is no less effective than in‐person treatment for the vast majority of presenting concerns (Varker, Brand, Ward, Terhaag, & Phelps, 2019) and that it can be an excellent extension to in‐person services such as aiding in assessment (Heesacker, Perez, Quinn, & Benton, 2020). Some seemingly obvious exceptions to this general rule may apply for specific clinical services, such as neuropsychological assessment, although evidence is mounting that certain neuropsychological assessments can feasibly be administered through telepsychology (Galusha‐Glasscock, Horton, Weiner, & Cullum, 2016).…”
Section: Telepsychology Special Issuementioning
confidence: 99%
“…The passage of the Patient Protection and Affordable Care Act (Obamacare) in March of 2010 triggered rapid growth in telehealth equipment, software, and electronic health record systems. Reviewing the randomized controlled trial literature from 2005 through 2016 regarding the telepsychological treatment of four mental health conditions (depression, anxiety, PTSD, and adjustment disorders) found evidence to support video conferencing and teleconferencing interventions (Varker, Brand, Ward, Terhaag, & Phelps, 2019). Campbell, Millan, and Martin (2018) in a series of case studies explored processes for informed consent in telepsychology, an important new practice development.…”
Section: The Emerging and Evolving World Of Telehealthmentioning
confidence: 99%
“…A number of studies have demonstrated telepsychology is an effective delivery method for a wide variety of psychotherapeutic interventions. A recent meta‐analysis was published (Varker, Brand, Ward, Terhaag, & Phelps, ) including 24 randomized control noninferiority trials comparing the efficacy of telepsychology versus in‐person therapy for anxiety, depression, post traumatic stress disorder, and adjustment disorder. Ten studies were included that investigated the effectiveness of telephone‐delivered interventions, 11 of video teleconference interventions, and two Internet‐delivered.…”
Section: Introductionmentioning
confidence: 99%